16p11.2 deletion syndrome. (June 2021) - Chung, Wendy K; Roberts, Timothy PL; Sherr, Elliott H; Snyder, LeeAnne Green; Spiro, John E
Abstract : The 16p11.2 BP4 and BP5 region, is a recurrent ∼600 kb copy number variant (CNV), and deletions are one of the most frequent etiologies of neurodevelopmental disorders and autism spectrum disorder with an incidence of approximately 1/2000. Deletion carriers have delays in early neurodevelopment that most specifically impair speech, phonology and language in 70%. Intelligence quotient is shifted 1.8 standard deviations lower than family controls without the deletion. Other common neurobehavioral conditions include motor coordination difficulties (60%) and autism (20–25%). Unprovoked seizures are common (24%) and readily treated and resolve with age in many. Obesity evolves throughout childhood and by adulthood 75% are obese. Congenital anomalies are more common than the general population. The deletion is associated with an increase in brain volumes across all areas of the brain, changes in the white matter microstructural properties, and early electrophysiological cortical responses from auditory cortex. Studies of genetically defined conditions, particularly CNVs that are not associated with profound disabilities, provide homogeneity to study genetic impact on brain development, structure, and function to better understand complex neurobehavioral phenotypes such as autism.